Socio-Demographic Factors Associated With COVID-19 Vaccine Hesitancy Among Middle-Aged Adults During the Quebec's Vaccination Campaign - Jantzen, Rodolphe; Maltais, Mathieu; Broët, Philippe (Frontiers in Public Health, 2022)
Introduction: The objective of this study was to characterize the combinations of demographic and socioeconomic characteristics associated to the unwillingness to receive the COVID-19 vaccines during the 2021 Quebec’s vaccination campaign. Materials and methods: In March-June 2021, we conducted an online survey of the participants of the CARTaGENE population-based cohort, composed of middle-aged and older adults. After comparing the vaccinated and unvaccinated participants, we investigated vaccine hesitancy among participants who were unvaccinated. For identifying homogeneous groups of individuals with respect to vaccine hesitancy, we used a machine learning approach based on a hybrid tree-based model. Results: Among the 6,105 participants of the vaccine cohort, 3,553 (58.2%) had at least one dose of COVID-19 vaccine. Among the 2,552 participants, 221 (8.7%) did not want to be vaccinated (91) or were uncertain (130). The median age for the unvaccinated participants was 59.3 years [IQR 54.7-63.9]. The optimal hybrid tree-based model identified seven groups. Individuals having a household income lower than 100,000 and being born outside of Canada had the highest rate of vaccine hesitancy (28% [95%CI 19.8-36.3]). For those born in Canada, the vaccine hesitancy rate among the individuals who have a household income below 50,000 before the pandemic or are non-retired was of 12.1% [95%CI 8.7-15.5] and 10.6% [95%CI 7.6-13.7], respectively. For the participants with a high household income before the pandemic (more than 100,000) and a low level of education, those who experienced a loss of income during the pandemic had a high level of hesitancy (19.2% [8.5-29.9]) whereas others who did not experience a loss of income had a lower level of hesitancy (6.0% [2.8-9.2]). For the other groups, the level of hesitancy was low of around 3% (3.2% [95%CI 1.9-4.4] and 3.4% [95%CI 1.5-5.2]). Discussion: Public health initiatives to tackle vaccine hesitancy should take into account these socio-economic determinants and deliver personalized messages towards people having socio-economic difficulties and/or being part of socio-cultural minorities.